Coexistence of fibromyalgia and metabolic syndrome in females: The effects on fatigue, clinical features, pain sensitivity, urinary cortisol and norepinephrine levels: A cross-sectional study - Onat ÇAKIT; Alper GÜMÜŞTEPE; Burcu DUYUR ÇAKIT; Seçil PERVANE VURAL; Tuba ÖZGÜN; Hakan GENÇ (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the coexistence of metabolic syndrome (MetS) and fibromyalgia syndrome (FMS) and determine the effects of this coexistence on neuroendocrine levels and clinical features of FMS. Patients and methods: One-hundred female FMS patients (mean age 40.1±7.8 years; range, 24 to 58 years) and 38 healthy females (mean age 40.4±5.8 years; range, 30 to 55 years) were included in this cross-sectional study. MetS was identified by using the criteria from the Adult Treatment Panel III. Widespread pain index, symptom severity score and number of tender points were determined. Visual analog scale, Fibromyalgia Impact Questionnaire, Fatigue Severity Scale, Beck Depression Inventory, and pain pressure threshold were used as the outcome measures. The severity of FMS was assessed with total myalgic score (TMS) and control point score. Results: Twenty-four (24%) of the 100 FMS patients and three (7.9%) of the 38 control patients fulfilled the MetS criteria (p=0.047). The coexistence of FMS and MetS was associated with higher symptom severity score (p=0.004), widespread pain index (p=0.001), number of tender points (p=0.039), and lower total myalgic score (p=0.029) values. There was a significant association between the occurrence of FMS and MetS (odds ratio=3.76; 95% confidence interval: 1.04-13.4; p=0.043). Conclusion: We found that patients with FMS had a nearly four times higher risk for MetS and the coexisting MetS may increase the severity of FMS. In clinical practice, when evaluating a patient with FMS, metabolic characteristics should also be evaluated.